Prevalence of use of permitted pharmacological substances for recovery among athletes - Elma Omeragic; Aleksandra Marjanovic; Jasmina Djedjibegovic; Amila Turalic; Mirza Dedic; Haris Niksic; Aida Lugusic; Miroslav Sober (Pensoft Publishers, 2021)
Objectives: Food supplements and medicines which are not on the list of prohibited substances of the World Anti-Doping Agency are included in the group of permitted pharmacological agents for athlete's recovery. The aim of this study was to describe qualitatively and quantitatively food supplements (FS) and over-the-counter drugs use among athletes in the last six month. Methods: This was a cross sectional study. Data on food supplements and the over-the-counter drugs, usage were collected during 2018 by self-administered, anonymous questionnaire. Results: A total of 112 athletes completed the survey. A total of 51.8% (n = 58) athletes reported the use of food supplements. The use of medical supplements was reported by 50.0% (n = 56) of athletes, 26.8% (n = 30) reported using ergogenic supplements, 1.8% (n = 2) using of sports food and 4.5% (n = 5) using other supplements. The use of over-the-counter drugs was reported by 35.7% (n = 40) of athletes. The over-the-counter analgesic drugs were used by 95% (n = 38) of over-the-counter drug users. Concomitant administration two or more over-the-counter drugs was reported by 40% (n = 16) athletes. Doctors and coaches had no advisory role in the use of food supplements or over-the-counter drugs.